Post-chemotherapy modified template retroperitoneal lymph node dissection in patients with nonseminomatous germ cell tumours - Zor, Murat; Yilmaz, Sercan; Topuz, Bahadir; Kaya, Engin; Yalcin, Serdar; Coguplugil, Adem Emrah; Ince, Mehmet Emin; Gurdal, Mesut (Aktuelle Urologie, 2021)
Introduction/background: Although a full bilateral template RPLND is thought to be the standard of care for the management of postchemotherapy retroperitoneal residual masses for nonseminomatous germ cell tumors (NSGCT), in the past decade modified templates have become increasingly popular. In this study, we aimed to present our oncological and perioperative outcomes of consecutive seventeen NSGCT patients who underwent a modified template unilateral PC-RPLND for retroperitoneal residual disease.Materials and Methods: We retrospectively evaluated the medical records of 17 consecutive NSGCT patients who underwent modified template unilateral PC-RPLND in our university hospital between 2017 and 2020. All patients had normal serum tumour markers with residual disease in the retroperitoneum. Surgical characteristics including the size of the retroperitoneal residual mass, residual tumor pathology, removed lymph nodes, positive percentage of removed lymph nodes, accompanying operations, complications, mean operation time and hospital stay, and long-term results including survival and antegrade ejaculation were evaluated.Results: Eleven patients underwent left and six right-sided surgery. Median residual lymph node diameter was 41mm. Median hospitalisation time was 3.5 days. Median follow-up time was 10.5 months. Necrosis/fibrosis was seen in 6 patients, and teratoma in 11 patients. No viable tumour was seen. No patients died in the follow-up period. None of the patients relapsed during follow-up. Ten/seventeen patients had antegrade ejaculation.Conclusions: Modified template unilateral PC-RPLND leads to very good oncological outcomes with decreased perioperative morbidity as well as better antegrade ejaculation rates. Low volume retroperitoneal disease seems to fit this procedure best.
Keywords: post-chemotherapy; retroperitoneal lymph node dissection; modified template; germ cell tumor; nonseminomatous